2020
DOI: 10.1016/j.ccell.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Gene Expression Landscape Profiling Approach to Identify Lung Tumor Endothelial Cell Heterogeneity and Angiogenic Candidates

Abstract: In the original article, the surname of co-author Wouter Everaerts was spelled incorrectly as "Everaert." It appears correctly in this Correction, and the error has been corrected online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
238
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(260 citation statements)
references
References 0 publications
20
238
1
1
Order By: Relevance
“…Consistent with the impaired tip cell phenotype, radial expansion of the vascular network was significantly inhibited in the Pdcd10 -ko retina ( Figure 5I , quantification in Figure 5J ). It remains to be explored whether these tip-like cells have features of the recently described breach cells of lung tumor vessels ( Goveia et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the impaired tip cell phenotype, radial expansion of the vascular network was significantly inhibited in the Pdcd10 -ko retina ( Figure 5I , quantification in Figure 5J ). It remains to be explored whether these tip-like cells have features of the recently described breach cells of lung tumor vessels ( Goveia et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent scRNA‐seq studies have determined that tumor endothelial cells are heterogeneous at a molecular level, and that the various subtypes contribute to angiogenesis and tumor progression and respond to targeting therapies in different ways 90‐92 . Detailed subtyping and a deeper understanding of this heterogeneity would require an extensive functional validation study, but would be helpful in establishing new therapeutic strategies beyond VEGF targeting.…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…To further characterize the SARS-CoV-2 entry factor transcript expression patterns in brain endothelial cells, we examined the different brain endothelial cell clusters according to their arterio-venous specification, as previously described in mouse brain 7880 (Figure 4a). We found that CTSB was expressed in multiple brain endothelial cell types including veins, capillaries, endothelial cells 1 (EC1), antigen presenting- and vein (antigen presenting) endothelial cells (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, recent studies using single-cell transcriptomics in human and mouse tissues revealed endothelial clusters in a variety of tissues including the human bladder, and kidney (and others) as well as the mouse and human lung expressing MCH class II genes such as HLA-DPA1 and HLA-DRA involved in MHC class II- mediated antigen processing, loading and presentation 80 .…”
Section: Resultsmentioning
confidence: 99%